2020
DOI: 10.1101/2020.09.09.289827
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ophthalmic Changes in a Spaceflight Analog Are Associated with Brain Functional Reorganization

Abstract: ImportanceFollowing long-duration missions onboard the International Space Station, some astronauts develop ophthalmic abnormalities collectively referred to as Spaceflight Associated Neuro-ocular Syndrome (SANS). Optic disc edema is a common sign of SANS. SANS presents significant potential risk to astronaut health and performance; however, the origin and effects of SANS are not understood as signs of SANS have not manifested in previous spaceflight analog studies.ObjectiveTo investigate whether development o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 70 publications
(129 reference statements)
1
9
0
Order By: Relevance
“…They underwent 60 days of 6° strict HDBR and performed a range of sensorimotor and cognitive tasks both in and out of the centrifuge at multiple time points prior to, during, and following the 60 day protocol. The measures implemented in this study overlap with those in our ongoing NASA supported flight and prior bed rest studies ( Koppelmans et al, 2013 ; Cassady et al, 2016 ; Yuan et al, 2016 , 2017 , 2018a , 2018b ; Hupfeld et al, 2019 , 2020 ; Lee et al, 2019 ; McGregor et al, 2020 , 2021 ; Salazar et al, 2020 , 2021 ; Banker et al, 2021 ; Mahadevan et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They underwent 60 days of 6° strict HDBR and performed a range of sensorimotor and cognitive tasks both in and out of the centrifuge at multiple time points prior to, during, and following the 60 day protocol. The measures implemented in this study overlap with those in our ongoing NASA supported flight and prior bed rest studies ( Koppelmans et al, 2013 ; Cassady et al, 2016 ; Yuan et al, 2016 , 2017 , 2018a , 2018b ; Hupfeld et al, 2019 , 2020 ; Lee et al, 2019 ; McGregor et al, 2020 , 2021 ; Salazar et al, 2020 , 2021 ; Banker et al, 2021 ; Mahadevan et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Here, we administered a similar battery of cognitive and sensorimotor assessments as we have previously applied in our HDBR and spaceflight studies ( Koppelmans et al, 2017 ; Cassady et al, 2016 ; Yuan et al, 2016 , 2017 , 2018a , 2018b ; Hupfeld et al, 2019 , 2020 ; McGregor et al, 2020 , 2021 ; Salazar et al, 2020 , 2021 ; Banker et al, 2021 ). Our primary aim in the current study was to examine whether centrifugal artificial gravity applied along the long axis of the body at approximately 1G at the center of mass modulates the effects of HDBR on sensorimotor and cognitive performance.…”
Section: Introductionmentioning
confidence: 99%
“…Further, we hypothesized that, compared with controls, the AG group would require lower levels of brain activation in task-related sensorimotor brain regions both during and following HDBR. The measures implemented in this study overlap with those in our ongoing NASA-supported flight and prior bed rest studies (Koppelmans et al, 2013; Yuan et al, 2018a; 2018b; Lee et al, 2019; Hupfeld et al, 2019; 2020; 2021 McGregor et al, 2020; 2021; Salazar et al, 2020; Banker et al, 2021).…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, this environment results in similar effects to microgravity such as reduced sensory inputs to the bottom of the feet, axial body unloading, and headward fluid shifts 19,20 . HDBR is also associated with subsequent postural and mobility declines as well as altered brain activity 2, 20-26 . Resting state functional MRI -an approach for estimating correlated neural activity across distributed brain networks 27 -has revealed changes in brain network functional connectivity (FC) with HDBR 24,25,[28][29][30][31][32] . Studies of short (72 hours 22,30 ) and longer (30-70 days [24][25][26]31,32 ) duration HDBR have revealed changes in FC from pre-to post exposure.…”
Section: Introductionmentioning
confidence: 99%
“…HDBR is also associated with subsequent postural and mobility declines as well as altered brain activity 2, 20-26 . Resting state functional MRI -an approach for estimating correlated neural activity across distributed brain networks 27 -has revealed changes in brain network functional connectivity (FC) with HDBR 24,25,[28][29][30][31][32] . Studies of short (72 hours 22,30 ) and longer (30-70 days [24][25][26]31,32 ) duration HDBR have revealed changes in FC from pre-to post exposure. For example, we previously found that 70 days of HDBR resulted in increased FC between motor and somatosensory brain regions; participants who showed FC increases between these regions the most had the smallest decrements in balance after exiting HDBR…”
Section: Introductionmentioning
confidence: 99%